Desire For Power In Sophocles's Antigone Drama (496 BC-406 BC): A Psychoanalytic Perspective - Andayani, Catur (2012)
The major problem of this study is how the desire for power is reflected in the major character's personality. The aim of this study is to analyze Sophocles's Antigone drama based on the structural elements and the development of personality of the major character based on Psychoanalytic Perspective. This study focuses on the major character, namely Creon. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is taking note, while the technique of Data Analysis in this study is descriptive. Based on the structural analysis it is evident that in this drama, Sophocles wants to deliver a message that desire for power can bring sufferings to ourselves and other people. Based on the psychological analysis, it clear that in Antigone drama Sophocles describes a psychological phenomenon, in which the major character, Creon has some qualities as ambitious to get the highest position and authority to achieve power.